Outcomes of oxygen saturation targeting during delivery room stabilisation of preterm infants. Issue 5 (7th October 2017) - Oei, Ju Lee; Finer, Neil N; Saugstad, Ola Didrik; Wright, Ian M; Rabi, Yacov; Tarnow-Mordi, William; Rich, Wade; Kapadia, Vishal; Rook, Denise; Smyth, John P; Lui, Kei; Vento, Maximo
Abstract : Objective: To determine the association between SpO2 at 5 min and preterm infant outcomes. Design: Data from 768 infants <32 weeks gestation from 8 randomised controlled trials (RCTs) of lower (≤0.3) versus higher (≥0.6) initial inspiratory fractions of oxygen (FiO2 ) for resuscitation, were examined. Setting: Individual patient analysis of 8 RCTs Interventions: Lower (≤0.3) versus higher (≥0.6) oxygen resuscitation strategies targeted to specific predefined SpO2 before 10 min of age. Patients: Infants <32 weeks gestation. Main outcome measures: Relationship between SpO2 at 5 min, death and intraventricular haemorrhage (IVH) >grade 3. Results: 5 min SpO2 data were obtained from 706 (92%) infants. Only 159 (23%) infants met SpO2 study targets and 323 (46%) did not reach SpO2 80%. Pooled data showed decreased likelihood of reaching SpO2 80% if resuscitation was initiated with FiO2 <0.3 (OR 2.63, 95% CI 1.21 to 5.74, p<0.05). SpO2 <80% was associated with lower heart rates (mean difference −8.37, 95% CI −15.73 to –1.01, *p<0.05) and after accounting for confounders, with IVH (OR 2.04, 95% CI 1.01 to 4.11, p<0.05). Bradycardia (heart rate <100 bpm) at 5 min increased risk of death (OR 4.57, 95% CI 1.62 to 13.98, p<0.05). Taking into account confounders including gestation, birth weight and 5 min bradycardia, risk of death was significantly increased with time taken to reach SpO2 80%. Conclusion: Not reaching SpO2 80% at 5 min is associated with adverse outcomes, including IVH. Whether this is because of infant illness or the amount of oxygen that is administered during stabilisation is uncertain and needs to be examined in randomised trials